Physio-Biochemical changes in lentil genotypes under biotic stress induced by Stemphylium botryosum Wallr - Shishir Rizal; Poly Saha; Partha Mondal; Md Sabir Ahmed Mondol; Jhuma Datta; Tayebeh Ahmadi; Mehdi Rahimi (BMC Plant Biology)
Abstract Stemphylium blight (SB) is a major biotic stress that poses a potential threat to total yield loss in lentils. In this context, a comparative study was devised on the biochemical and physiological changes that may occur in six tolerant/resistant and six susceptible/highly susceptible lentil genotypes that were inoculated with the SB pathogen. Pathogen inoculation significantly reduced total chlorophyll and relative leaf water content across all genotypes, with the greatest reduction observed in susceptible genotypes. The recorded membrane stability index indicated significant membrane damage due to pathogen inoculation, particularly in susceptible genotypes. Similarly, the proline, total soluble protein, total soluble sugar, total phenol, and ascorbic acid contents increased several-fold in resistant genotypes when the pathogen was inoculated. Resistant lentil genotypes accumulated relatively high levels of antioxidant enzymes such as peroxidase, catalase, polyphenol oxidase, and phenyl ammonium lyase, while susceptible genotypes exhibited relatively low accumulation after pathogen inoculation. Pathogenesis-related enzymes like β- 1,3-glucanase, and chitinase were notably upregulated in the resistant genotypes compared to the susceptible genotypes. Fourteen biochemical parameters recorded from the screened genotype were subjected to principal component analysis (PCA). The results revealed that β- 1,3-glucanase, proline, ascorbic acid and chitinase activity were found to be excellent determinants of susceptibility or resistance of a particular genotype. In conclusion, it can be inferred that genotypes: G- 17 (7979/DPL62/2), G- 31 (8114/10956/16–1) and G- 13 (ILL10838/ILWL11/X2016S) exhibited favourable performance in terms of disease tolerance.